2004
DOI: 10.1080/14659890410001665096
|View full text |Cite
|
Sign up to set email alerts
|

Screening and brief alcohol interventions: What, why, who, where and when? A review of the literature

Abstract: There is a significant body of literature in the field of screening and brief alcohol intervention. This paper reviews that literature in order to provide a comprehensive overview of this important field of study. The format of the paper is not intended to be one of a systematic review with meta-analysis, but rather a gathering of data to give readers a concise summary of the vast quantity of literature relating to screening and brief alcohol intervention. The review will provide a working definition of screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…When teaching the use of MCII, the experimenter had emphasized the understanding of the logic underlying MCII to facilitate its application to any upcoming concerns in the subsequent week. This approach is in contrast to most existing interventions aimed at behavior change, which typically tell people how to strive for an a priori defined desired outcome (e.g., weight control, Stice, Shaw, & Marti, ; alcohol control, Lock, ; forgiveness, Harris et al, ). Such focus on specific outcomes has also been true of most interventions geared at improving time management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When teaching the use of MCII, the experimenter had emphasized the understanding of the logic underlying MCII to facilitate its application to any upcoming concerns in the subsequent week. This approach is in contrast to most existing interventions aimed at behavior change, which typically tell people how to strive for an a priori defined desired outcome (e.g., weight control, Stice, Shaw, & Marti, ; alcohol control, Lock, ; forgiveness, Harris et al, ). Such focus on specific outcomes has also been true of most interventions geared at improving time management.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, MCII was applied to a pressing academic concern (Study 1) or acquired as a metacognitive strategy (i.e., the skill to use a certain set of cognitive procedures on appropriate thought contents; Studies 2 and 3); still, it was found to have the ancillary benefit of aiding time management. Apparently, not only behavior change interventions focusing on desired outcomes that are a priori defined (e.g., weight control, Stice et al, ; alcohol control, Lock, ; forgiveness, Harris et al, ) achieve benefits. Interventions that teach metacognitive strategies to be applied to a host of everyday concerns are also beneficial (Achtziger, Martiny, Oettingen, & Gollwitzer, ; Oettingen, ).…”
Section: Discussionmentioning
confidence: 99%
“…This has been a focus in recent years, resulting in the dissemination of various effective screening tools for use in primary care settings (Brown, Leonard, Saunders, & Papasouliotis, 2001;Fiellin, Reid, & O'Connor, 2000;Fornili & Haack, 2005). However, the use of these tools by primary care providers remains limited (Armstrong & Holmes, 2005) and practitioners identify challenges to incorporating screening protocols in practice (Lock, 2004;Vandermause, 2007;Vinson, Elder, Werner, Vorel, & Nutting, 2000). One way to examine this problem is to address the questioning process itself.…”
Section: Introductionmentioning
confidence: 93%
“…General practitioners (GPs) and community pharmacists are well placed to provide information and advice on a range of health-related topics to a diverse cross section of the community, [1][2][3][4] and perform an important primary health care role. [2,5] However, despite a range of international studies highlighting the feasibility and effectiveness of community pharmacists and GPs providing alcoholrelated health information to the general public, [6][7][8][9][10][11][12][13] most have focused on health professionals' experiences and perceptions, [1,6,8,14] with only a few investigating the public's views on acceptability and value of health information delivered through primary health care services, [6,9,10,13,15] and even less exploring older people's perspectives.…”
Section: Introductionmentioning
confidence: 99%